1981
DOI: 10.1242/jeb.94.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Activity and Relative Length Changes of Dog Limb Muscles as A Function of Speed and Gait

Abstract: Electrical activity and length changes of 11 muscles of the fore- and hind- limbs of dogs walking, running, and galloping on a treadmill, were measured as a function of forward speed and gait. Our purpose was to find out whether the activity patterns of the major limb muscles were consistent with the two mechanisms proposed for storage and recovery of energy within a stride: a ‘pendulum-like’ mechanism during a walk, and a ‘spring-like’ mechanism during a run. In the stance phase of the walking dog, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…There is considerable evidence that mammalian movement is organized so that gravity or the elastic components of the actuators can be used to store mechanical energy and return it, thereby reducing metabolic energy consumption (Cavagna et al, 1977; Fedak et al, 1982; Heglund et al, 1982; Hof et al, 1983; Taylor, 1980). For instance, walking is organized as a combination of inverted and upright pendulums (Alexander, 1977; McMahon, 1984; Mochon & McMahon, 1980), while running takes advantage of the elastic compliance of muscles and tendons (Alexander, 1984; Giovanni et al, 1980; Goslow, Seeherman, Taylor, McCutchin, & Heglund, 1981; Taylor et al, 1980). Such organization produces preferred frequencies that reflect the optimal frequencies at which mechanical energy can be conserved via the particular storage medium (Cavagna et al., 1977; Mochon & McMahon, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence that mammalian movement is organized so that gravity or the elastic components of the actuators can be used to store mechanical energy and return it, thereby reducing metabolic energy consumption (Cavagna et al, 1977; Fedak et al, 1982; Heglund et al, 1982; Hof et al, 1983; Taylor, 1980). For instance, walking is organized as a combination of inverted and upright pendulums (Alexander, 1977; McMahon, 1984; Mochon & McMahon, 1980), while running takes advantage of the elastic compliance of muscles and tendons (Alexander, 1984; Giovanni et al, 1980; Goslow, Seeherman, Taylor, McCutchin, & Heglund, 1981; Taylor et al, 1980). Such organization produces preferred frequencies that reflect the optimal frequencies at which mechanical energy can be conserved via the particular storage medium (Cavagna et al., 1977; Mochon & McMahon, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Note that, in contrast with the previous consideration of a single four-bar linkage tuned to achieve very nearly straight-line motion, the approach here (and below, for the hindlimb) calculates the series of linkages – each with a different muscle ray as one of the links – that achieves exactly straight-line motion, the joints of each linkage undergoing infinitesimally small changes in angle over the course of its engagement. The isometric but active nature of the triceps during weight support has previously been alluded to through geometric analysis and EMG recordings ( Goslow et al, 1981 ); however, at that time, the functional implication of such loading was constrained to an assumption of benefit from elastic loading and recoil. The paradigm proposed here is that the broadly isometric loading of the triceps contributes to near-straight-line, vertical-force, low-power weight support.…”
Section: The Forelimb As a Series Of Four-bar Linkagesmentioning
confidence: 99%
“…It has been reported that forelimb and hindlimb gait movements strongly influence thoracic and lumbar motion, respectively [ 133 ]. In the standing position, the load in the vertical direction is more strongly applied to the forelimb than to the hindlimb, with a ratio of at least 6:4 [ 133 , 134 , 135 , 136 , 137 ], which suggests that the forelimbs are mainly loaded from the early stage at the initiation of walking. Owing to the strut load, dystrophic dogs might experience muscle involvement, especially in the forelimb, before the onset of muscle weakness, which could lead to reduced acceleration in the thoracic region.…”
Section: Motor Function Evaluations With Accelerometrymentioning
confidence: 99%